Modelización directa y comparación de los principales dispositivos geoeléctricos - Arias Salguero, Mario E. (Universidad de Costa Rica, 2009)
With the purpose of comparing the main geolectrics arrays used for the realization of vertical electrical sounding, a direct simulation is presented, considering two geologic models. The investigation depth, precision in the determination of the thickness of the layers, the effects of the presence of a superficial layer, the geometric similarity and the sensibility to the mensuration of the potential difference are evaluated. It is considered that the most appropriate arrays for vertical electrical sounding are those of Wenner and of Schlumberger. On the other hand; the pole-pole and the dipole-dipole should be used preferably for geolectrics profiles (constant separation transversing) and electrics pseudosections.